Unsustainable transport : city transport in the new century: the transport crisis - Banister, D (Routledge, 2005)
This book addresses the links between transport and sustainable urban development, from an analysis of the global picture to issues in transport and energy intensity, public policy and the institutional and organisational constraints on change. The central part of the book explores these links in more detail at city level, covering land use and development, economic measures, and the role that technology can play. The final part looks for inspiration from events in developing countries and the means by which we can move from the unsustainable present to a more sustainable future.